"Attractor Tempi" in Brahms's Symphony No. 2/III. (2nd May 2018) - Gotham, Mark R H
Abstract: This analysis assesses tempo choice in the third movement of Brahms's Second Symphony. It is shown that, at key moments of the movement, the average tempi used in a sample of commercial recordings align closely with those suggested by the "attractor" model of cognitively preferable (easiest) tempi (Gotham 2015 ). Between these stable checkpoints, the movement navigates through a variety of other metrical structures at (formally) the same tempo, each with their own attractor tempi. These necessarily align less well with the tempi used, thus providing a pattern of relative tension/relaxation, which the new model helps to elucidate.